Perencanaan Konstruksi Dinding Penahan Tanah Pada Jalan Takengon-Blangkejeren II - verawati fajaryana; Ichsan Syahputra; Muhammad Ridha (Jurnal Teknik Sipil Unaya, 2022)
The purpose of this final project is to determine the dimensions of the cantilever type retaining wall, to calculate the stability factor of safety (FS) against overturning,shear and the bearing capacity of the soil and to plan the dimensions of the retaining wall reinforcement on the Takengon-Blangkejeren II road. Data collection is done by direct observation in the field, and research in the laboratory. The research procedures in the laboratoty are: soil sampling in the field, the number of soil samples taken, soil sampling techniques, and testing of soil mechanical properties. Testing the mechanical properties of the soil in the form of Direct Shear testing. The result showed that in the laboratory test the soil was sandy silt and silty sand, so that the weight of the soil volume by taking the average value was 17,65 kN/m3, the cohesion value (c) was 0,0272 kg/cm2, the shear angle ( ) obtained 14,56 on the soil sample HB01. In the HB02 soil sample, the weight of the soil volume  was  17,65 kN/m3, the cohesion value (c) was 0,0188 kg/cm2, and the shear angle ( ) was 13,03  in the HB02 soil sample. So that the planned dimensions of the retaining wall are with dimensions H = 6,00 m, B = 3,60 m, qtoe width = 0,60 m, qheel width = 2,40 m.